ANALISIS JANGKAUAN HALTE TRANSPADANG TERHADAP PENDIDIKAN DI KECAMATAN KURANJI - Elisa Maiyenti (Department of Civil Engineering, Faculty of Engineering, Universitas Negeri Padang, 2025)
This study aims to analyze the coverage of TransPadang bus stops in relation to educational facilities in Kuranji District, Padang City. The method used is spatial analysis based on Geographic Information System (GIS) with a buffer technique of 500 meters from the location of TransPadang bus stops. The data analyzed included the distribution of TransPadang bus stops, bus routes, and formal educational facilities such as elementary schools, junior high schools, high schools, and universities, which had been validated through field surveys. The results of the analysis show that TransPadang bus stops tend to be spread along main road corridors, while educational facilities have a diverse distribution pattern. Some educational facilities are within the service range of bus stops and are categorized as served, while others are outside the range and are not yet directly served. The results of this study indicate that the TransPadang public transportation service to educational facilities in Kuranji District is not yet evenly distributed and still requires service network development.